2003
DOI: 10.4028/www.scientific.net/msf.414-415.385
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Semi-Empirical Method to Select the Processing Parameters for Laser Clad Coatings

Abstract: A semi-empirical method for selecting the processing parameters of laser cladding is proposed. This phenomenological approach uses simple mathematical formulae, derived from a statistical analysis of measured data, to relate the laser cladding parameters with the geometric features of the clad track. Given the prescribed clad height and available laser beam power, the proposed method allows to calculate values of the scanning speed and powder feed rate which are required to obtain low dilution, pore free coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…It was reported earlier that formation of eutectic carbides is related to dilution effect with the substrate; the higher the dilution, the higher the formation of phases containing iron thus decreasing the formation of carbides [11,29]. In addition, a According to the abovementioned results, the cladding characteristics encountered here (i.e., porosity, dilution, and width) are an indication of a highly dense and well-bonded clad tracks [28] without any presence of cracks.…”
Section: Microstructure and Phasessupporting
confidence: 68%
See 1 more Smart Citation
“…It was reported earlier that formation of eutectic carbides is related to dilution effect with the substrate; the higher the dilution, the higher the formation of phases containing iron thus decreasing the formation of carbides [11,29]. In addition, a According to the abovementioned results, the cladding characteristics encountered here (i.e., porosity, dilution, and width) are an indication of a highly dense and well-bonded clad tracks [28] without any presence of cracks.…”
Section: Microstructure and Phasessupporting
confidence: 68%
“…It has been established that an acceptable range for dilution in WC-Co is within 10-45% for a single clad track [8,26]; accordingly, acceptable values for dilution are obtained in this work. According to the abovementioned results, the cladding characteristics encountered here (i.e., porosity, dilution, and width) are an indication of a highly dense and well-bonded clad tracks [28] without any presence of cracks.…”
Section: Microstructure and Phasessupporting
confidence: 58%
“…The following selected examples provide a sense of the processing parameter values used in LPD and cross‐sectional characteristics of the resulting individual material tracks:Koch and Mazumder (1993) performed LPD of aluminum using a CO 2 laser: a 4,000 W laser beam focused into a 3.5 mm diameter spot was used to fuse the feedstock material, delivered at 11.0 g/min by a lateral powder feeding nozzle, into single clad tracks 0.4 mm thick and 4 mm wide, deposited at a rate of 2,540 mm/min.Kreutz et al (1995) reported on LPD of Stellite 6 using a CO 2 laser: a 4,000 W laser beam focused into a 6 mm diameter spot was used to fuse the feedstock material, delivered at 100 g/min by a lateral powder feeding nozzle, into single clad tracks 1 mm thick and 6‐8 mm wide, deposited at a rate of 300 mm/min.Mazumder et al (1997) reported on LPD of AISI H13 tool steel using a CO 2 laser: a 1,000 W laser beam focused into a 0.6 mm diameter spot was used to fuse the feedstock material, delivered at 5 g/min by a coaxial powder feeding nozzle, into single clad tracks 0.25 mm thick and 0.6 mm wide, deposited at a rate of 750 mm/min.Milewski et al (1998b) reported on LPD of 316 SS using a Nd:YAG laser: a 400 W laser beam focused into a 0.5 mm diameter spot was used to fuse the feedstock material, delivered at 2 g/min, into single clad tracks 0.1 mm thick and 0.5 mm wide, deposited at a rate of 1,260 mm/min.Hofmeister et al (2001) reported on LPD of AISI 316 SS using a Nd:YAG laser: a 360 W laser beam was used to fuse the feedstock material, delivered at 132 mm 3 /min, into 0.5 mm thick layers, at 508 mm/min.Pinkerton and Li (2004c) reported on the LPD of AISI 316L SS using a diode laser: a 700 W “top‐hat” 3.8×4.3 mm 2 laser beam was used to fuse the feedstock material, delivered at 12‐18 g/min, into single clad tracks 0.8 mm thick and 2.2 mm wide, deposited at a rate of 300 mm/min.Gremaud et al (1996) reported on the LPD of various materials, including IN625, using a CO 2 laser: a 1,500 W laser beam focused into a 3.0 mm diameter spot was used to fuse the IN625 powders, delivered at 7 g/min, into single clad tracks 0.36 mm thick and 2.2 mm wide, deposited at a rate of 700 mm/min.Lewis and Schlienger (2000) reported on the LPD of Inconel 690 using a Nd:YAG laser: a 160 W laser beam focused into a 0.5 mm diameter spot was used to fuse the feedstock material, delivered at 9 g/min, into single clad tracks 0.25 mm thick, deposited at a rate of 762 mm/min.Meacock and Vilar (2008) reported on laser microdeposition of CP2 Titanium using a CO 2 laser: a 130 W laser beam focused into a 0.3 mm diameter spot was used to fuse the feedstock material, delivered at 0.14 g/min, into single clad tracks 0.12 mm thick and 0.3 mm wide, deposited at a rate of 240 mm/min.Changes to both the material deposition rate and to the shape and dimensions of the transverse cross‐section of individual material tracks with variation of processing parameter values are a frequent topic within the LPD literature (Weerasinghe and Steen, 1983, 1987; Colaço et al , 1994, 1996; Gremaud et al , 1996; Mazumder et al , 1999; Kobryn et al , 2000; Kreutz et al , 1995; Costa et al , 2003b; Oliveira et al , 2005; Ma...…”
Section: Materials Deposition Capabilities Of Laser Powder Depositionmentioning
confidence: 99%
“…Lower part of Figure 1shows an example of laser clad tool steel coating formed by 33.3% overlap of individual laser tracks. The most common functions present in the literature describing the section profile of a single welding and laser cladding tracks are parabolic or circular arc segments [1][2][3][4][5][6][7]. It was observed experimentally that the parabolic profile is more realistic for tracks with a high H/w ratio, whilst the circle segment fits the track profile better when the ratio is smaller [1,8].…”
Section: Figurementioning
confidence: 99%